A non-linear hyperbolic equation - Eliana Henriques de Brito (International Journal of Mathematics and Mathematical Sciences, 1980)
In this paper the following Cauchy problem, in a Hilbert space H, is considered: (I+λA)u″+A2u+[α+M(|A12u|2)]Au=fu(0)=u0u′(0)=u1